Bioactive silver phosphate/polyindole nanocomposites. Issue 19 (17th March 2020) - Podder, Soumik; Paul, Samrat; Basak, Piyali; Xie, Bowen; Fullwood, Nigel J.; Baldock, Sara J.; Yang, Ying; Hardy, John G.; Ghosh, Chandan K.
Abstract : Materials capable of releasing reactive oxygen species (ROS) can display antibacterial and anticancer activity, and may also have antioxidant capacity if they suppress intracellular ROS ( e.g. nitric oxide, NO) resulting in anti-inflammatory activity. Abstract : Materials capable of releasing reactive oxygen species (ROS) can display antibacterial and anticancer activity, and may also have anti-oxidant capacity if they suppress intracellular ROS ( e.g. nitric oxide, NO) resulting in anti-inflammatory activity. Herein we report silver phosphate (Ag3 PO4 )/polyindole (Pln) nanocomposites which display antibacterial, anticancer and anti-inflammatory activity, and have therefore potential for a variety of biomedical applications.